Analisis Tindak Tutur sebagai Strategi Marketing pada Iklan Minuman di YouTube Indonesia - Syafran, Ahmad (Crises on Languages and Literature, 2025)
This study aims to analyze the specific characteristics and themes in the eight leading drink advertisements, focusing on how illocutionary speech acts influence consumer behavior and perceptions of drink brands. This paper delves into locutionary and illocutionary speech acts in drink advertisements in Indonesia for the period 2022-2023, published on YouTube. This study focuses on the communicative forms and functions of illocutionary speech acts in drink advertising on YouTube during the 2022-2023 period. In addition to speech modes, the marketing product also uses other modes. The focus of this research will be dissected using Wijana's theory of illocutionary speech acts. The results showed that during the 2022-2023 period, there were 8 top drink advertisements in Indonesia. Among all the drink advertisements, 3 used representative speech, 10 used expressive speech, and one used directive speech functions for each communicative function. Additionally, this research revealed notable differences in the effectiveness of various types of speech acts across these advertisements, ultimately providing insights into their impact on marketing strategies within the beverage industry.